Kontekstualisasi Hadis-Hadis Walimatul Urs: Studi Tentang Kewajiban Menghadiri Pesta Nikah di Malaysia - Aufa , Nurul; Irwan, Irwan (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2024)
This study aims to analyze the guidelines for attending walimah based on the Hadiths of the Prophet Muhammad SAW and to assess the relevance and application of these guidelines in the current context in Malaysia. The primary focus of this study is to explore how the principles of walimah as taught in the Hadiths can be applied within the cultural and social context of contemporary Malaysian society, which may differ significantly from the historical context of these teachings. The research methodology used is qualitative with a normative legal approach. This study also involves a comparative analysis to contrast the implementation of walimah in the past with current practices. Data for this study were collected through a review of recent literature, interviews with village residents, and direct observation of wedding ceremonies in various communities across Malaysia. The findings indicate that the fundamental principles of Islam regarding walimah, such as the obligation to attend walimah and the importance of celebrating marriage openly, remain relevant and accepted by society. However, there is variation in the practice of walimah influenced by local customs and cultural developments. Some changes in the implementation of walimah were found, including adaptations to contemporary social and economic norms, but the core religious principles continue to be upheld. [Kajian ini bertujuan untuk menganalisis ketentuan mengenai kehadiran walimah berdasarkan hadis-hadis Nabi SAW dan menilai relevansi serta penerapan hukum tersebut dalam konteks masa kini di Malaysia. Fokus utama kajian ini adalah untuk mengeksplorasi bagaimana prinsip-prinsip walimah yang diajarkan dalam hadis dapat diterapkan dalam konteks budaya dan sosial masyarakat Malaysia saat ini, yang mungkin mengalami perbedaan signifikan dari konteks zaman dan tempat asalnya. Metode penelitian yang digunakan adalah penelitian kualitatif dengan pendekatan hukum normatif. Penelitian ini juga melibatkan analisis komparatif untuk membandingkan pelaksanaan walimah di masa lalu dengan praktik masa kini. Data untuk kajian ini dikumpulkan melalui penelusuran literatur terbaru, wawancara dengan penduduk kampung, serta observasi langsung terhadap pelaksanaan majlis perkahwinan di berbagai komunitas di Malaysia. Hasil penelitian menunjukkan bahwa prinsip-prinsip asas dalam Islam mengenai walimah, seperti kewajiban menghadiri walimah dan pentingnya merayakan pernikahan secara terbuka, masih relevan dan diterima oleh masyarakat. Namun, terdapat variasi dalam cara pelaksanaan walimah yang dipengaruhi oleh adat setempat dan perkembangan budaya. Beberapa perubahan dalam tata cara pelaksanaan walimah ditemukan, termasuk adaptasi terhadap norma sosial dan ekonomi kontemporer, namun prinsip dasar ajaran agama tetap dipertahankan].